Triple inhaled therapy for chronic obstructive pulmonary disease. Issue 11 (November 2016) - Montuschi, Paolo; Malerba, Mario; Macis, Giuseppe; Mores, Nadia; Santini, Giuseppe
Highlights: Triple therapy in a single inhaler is a new therapeutic option for COPD. Three fixed dose combinations of inhaled corticosteroids LABA and LAMA are in Phase III of clinical development. One fixed dose combination of MABA/inhaled corticosteroid is in Phase II of clinical development. Triple therapy might be particularly useful in selected COPD phenotypes. Abstract : Combining individual drugs in a single inhaler is the most convenient way to deliver triple therapy. A long-acting muscarinic receptor antagonist (LAMA) added to an inhaled corticosteroid (ICS)/long-acting β2 -adrenoceptor agonist (LABA) fixed-dose combination (FDC) can improve efficacy of pharmacological treatment of patients with chronic obstructive pulmonary disease (COPD). New inhaled ICS/LABA/LAMA FDCs, including fluticasone furoate/vilanterol/umeclidinium, budesonide/formoterol/glycopyrronium and beclometasone/formoterol/glycopyrronium, are in Phase III of clinical development for COPD. Triple inhaled therapy might be particularly useful in patients with severe to very severe COPD, above all in those with peripheral blood or sputum eosinophilia, asthma–COPD overlap syndrome (ACOS) or frequent exacerbators. Future prospective studies should assess efficacy and safety of triple ICS/LABA/LAMA therapy in selected COPD phenotypes.